Lack of patient involvement in care decisions and not receiving written discharge instructions are associated with unplanned readmissions up to one year - Kyle Kemp; Hude Quan; Maria Santana (The Beryl Institute, 2017)
This retrospective, cross-sectional study examined the relationship between aspects of inpatient communication and discharge instructions and unplanned, all-cause readmissions using individual-level data up to one-year post-discharge. Patients completed the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) telephone survey within 6 weeks of hospital discharge in Alberta, Canada. Survey data were linked to corresponding inpatient records. Independent variables included selected demographic characteristics, clinical variables, and five survey questions: a) patient involvement in care decisions, b) receiving written information at discharge, c) understanding the purpose of taking medications, d) understanding responsibility for one's health, and e) discussing help needed when returning home. From April 2011 to March 2014, 24,869 patients with a mean age of 52.8±19.8 years (range=18-100) were included. 18.6% of patients (n=4,821) experienced an unplanned hospital readmission within 43 to 365 days post-discharge. In adjusted, logistic regression models, patients who felt they were not involved in care decisions were more likely to be readmitted (OR=1.34; 95%CI: 1.17-1.53), as were patients who reported not receiving written information about signs and symptoms to watch out for post-discharge (OR=1.24; 95%CI: 1.15-1.35). Odds of readmission did not differ according to understanding of medications, understanding responsibility for one's health, or discussion of help needed when returning home. This study provides objective data, showing that specific hospital actions are associated with unplanned readmissions. It is an example of how patient-reported measures may be linked to administrative data to drive quality improvement initiatives.